2017
DOI: 10.1007/s00401-017-1669-y
|View full text |Cite
|
Sign up to set email alerts
|

Marginal vitamin A deficiency facilitates Alzheimer’s pathogenesis

Abstract: Deposition of amyloid β protein (Aβ) to form neuritic plaques in the brain is the unique pathological hallmark of Alzheimer's disease (AD). Aβ is derived from amyloid β precursor protein (APP) by β- and γ-secretase cleavages and turned over by glia in the central nervous system (CNS). Vitamin A deficiency (VAD) has been shown to affect cognitive functions. Marginal vitamin A deficiency (MVAD) is a serious and widespread public health problem among pregnant women and children in developing countries. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 66 publications
1
44
0
Order By: Relevance
“…C99 is then cleaved by γ-secretase at the transmembrane domain to shed the N-terminal fragment Aβ. Mutations enhancing β-cleavage of APP or altering γ-cleavage of C99 result in early-onset AD (3)(4)(5). Recently, a missense mutation in the APP gene was shown to suppress Aβ production and reduce the risk of AD (3,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…C99 is then cleaved by γ-secretase at the transmembrane domain to shed the N-terminal fragment Aβ. Mutations enhancing β-cleavage of APP or altering γ-cleavage of C99 result in early-onset AD (3)(4)(5). Recently, a missense mutation in the APP gene was shown to suppress Aβ production and reduce the risk of AD (3,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…All trans retinoic acid (atRA) is the functional form of VA in the body, and atRA plays an important role in the maturation of the central nervous system (CNS) during embryonic development by activating transcriptional factors, including retinoic acid (RA) nuclear receptors (RARs/RXRs) . Our previous studies have shown that gestational VAD impaired learning and memory skills in gestational VAD pups and that marginal VAD in early life could facilitate the pathogenesis of Alzheimer's disease . Our studies indicate that VA is involved in the pathogenesis of neurological diseases.…”
Section: Introductionmentioning
confidence: 72%
“…AD is the most common neurodegenerative disorder leading to dementia, and its pathologic features include amyloid plaques and neurofibrillary tangles (31)(32)(33). Cognitive decline is one of the major consequences of diabetes, and growing evidence supports a strong link between AD-related dementia and diabetes (24,(34)(35)(36)(37). The prevalence of mild cognitive impairments is dramatically increased in individuals with diabetes (38,39), and diabetes also significantly accelerates the progression from mild cognitive impairments to dementia (40).…”
Section: Discussionmentioning
confidence: 99%
“…Mice with blood glucose levels .13 mM were considered diabetic. After 6 wk of treatment, the Morris water maze test was performed as previously described (24).…”
Section: Fa and Stz Treatmentsmentioning
confidence: 99%